Religiosity, ethnocentrism end corporate image towards the perception of young muslim consumers: structural equation modelling approach - Haque, A. K. M. Ahasanul; Rahman, Sabbir; Haque, Mahmudul (EuroJournals Publishing, Inc., 2011)
The purpose of this research is to study the relationship between religiosity, ethnocentrism and corporate image towards the perception of purchasing foreign goods by the young Muslim consumers in Malaysia. A total of 250 questionnaires were distributed for measuring the relationship from young Muslim consumers in Klang Valley area. Finally, 230 questionnaires became validated and tested for further statistical analysis through exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and structural equation modelling (SEM) was applied for testing the hypotheses of the study. Among all the variables, corporate image and ethnocentrism behavior plays the most significant on the perception of young Muslim consumer’s before purchasing foreign made products. The added value of this paper is to link between theory and practice, and explore the religiosity and ethnocentrism behavior on young Muslim consumer’s purchase decisions of foreign products. Few researches have conducted over the years under the young Muslim consumers that investigated the relationship between religiosity and ethnocentrism perspective. Moreover, this relatively new issue remains largely undiscovered by researchers under various market environments.